A New Miniaturized Lizard From the Late Eocene of France and Spain. Issue 3 (31st January 2014) - Bolet, Arnau; Augé, Marc; Daza, Juan D.; Miller, Scott C.
Abstract We report here a new lizard genus and species shared by two late Eocene localities situated at both versants of the present Pyrenees (South‐Western Europe), one located in France (Escamps, MP19), and the other in Catalonia, Spain (Sossís, MP17a). The recovered specimens are remarkable because of their small size and peculiar morphology. Features of the dentary are interpreted as adaptations to a fossorial or semi‐fossorial lifestyle, although such modifications obscure the exact phylogenetic relationships of the new taxon. We suggest that it might represent a further example of scincoid lizard that independently achieved adaptations for burrowing or surface‐dwelling. This taxon reinforces the hypotheses that link the Southern Pyrenean assemblages to those from France rather than to those of the rest of the Iberian Peninsula, which are supposed to be somehow isolated and endemic to a certain degree during the middle and late Eocene, forming part of the so‐called Western Iberian Bioprovince. Anat Rec, 297:505–515, 2014. © 2014 Wiley Periodicals, Inc.